LITERATURE REVIEW: EFEKTIVITAS PENERAPAN REKAM MEDIS ELEKTRONIK DI FASILITAS PELAYANAN KESEHATAN - Ghandys Freecylia Aristya; Nurhafidah Nurhafidah; Pradea Wulandari (Ensiklopedia Research and Community Service Review, 2026)
The implementation of Electronic Medical Records (EMR) represents a strategic initiative to enhance the effectiveness of healthcare services through information technology. Although EMR systems have been widely implemented across healthcare facilities, variations in their effectiveness remain evident. This study aimed to analyze the effectiveness of EMR implementation in healthcare facilities based on system quality, information quality, service quality, system use, user satisfaction, and net benefits. A systematic literature review was conducted using the PRISMA approach. Article searches were performed in Google Scholar, Garuda, PubMed, and ScienceDirect databases, focusing on original research published between 2015 and 2025. Of the 1,007 articles initially identified, 20 of the most relevant studies were included and analyzed using descriptive narrative synthesis. The findings indicate that system quality, information quality, and service quality are associated with EMR use and user satisfaction. User satisfaction serves as an important component in assessing system effectiveness and the attainment of net benefits, including improved work efficiency, service quality, data accuracy, and organizational performance. However, challenges related to system interoperability, human resource readiness, and technical support remain substantial. In conclusion, the effectiveness of EMR implementation requires the integration of technological, organizational, and user-related aspects to support sustainable use in healthcare facilities. Keywords: Effectiviveness, Electronic Medical Records, Health Information Systems, Healthcare Facilities, DeLone and McLean